PERENCANAAN INTERNALISASI PENDIDIKAN ISLAM MODERAT - Fransiska, Jenny (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The aim of this research is to investigate the moderate Islamic education concept program at MIN 1 Rejang Lebong, including the steps, obstacles, support, and efforts involved. This research used qualitative methods and was conducted at MIN 1 Rejang Lebong. Data collection techniques include interviews, field research, and documentation studies. Data analysis techniques involve data reduction, analysis of available data, and conclusions. Research findings at MIN 1 Rejang Lebong identified four concepts: using future life skills to combat violence or learning through the principles of Ahlu Sunnah Wal Jama'ah An-Nahdiyin. At MIN 1 Rejang Lebong, these concepts include Islamic brotherhood (ukhuwah Islamiah), national brotherhood (ukhuwah wathaniyah), and human brotherhood (ukhuwah Insaniyah). MIN 1 Rejang Lebong focuses on two concepts: Islamic education (al-Islam) and Muhammadiyah principles (Kemuhammadiyahan).